Pengaruh Green Human Resource Management, Green Transformational Leadership, dan Green Organizational Culture Terhadap Green Employee Behavior pada PT Shinta Konveksi di Boyolali - Ihsan Agung Prakosa; M. Farid Wajdi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study's overarching goal is to dissect how PT Shinta Konveksi's Boyolali location's green HRM, green transformational leadership, and green organizational culture affect green employee behavior. This study relies on numerical data. All 180 workers of PT Shinta Konveksi made up the study's population. Probability sampling is used as a sample approach in this study. There were 125 participants in this research, and the sampling method utilized was simple random sampling. Primary data is required for this study. This study's primary data came from surveys given out to employees at PT Shinta Konveksi Boyolali. In this study, the Structural Equation Model (SEM) with partial least squares (Smart-PLS) was used for data analysis. This study's findings demonstrate a favorable and statistically significant relationship between Green HRM and Green Employee Behavior. This is supported by the fact that the original sample value was 0.250, the value of t-statistic was 3.609 (higher than 1.96), and the value of p-value was as large as 0.000 (less than 0.05). Employees' Green Behavior is Positively and Significantly Affected by Green Transformational Leadership. The results show that this is true: the original sample value was 0.338, the t-statistic was 4.642 (higher than 1.96), and the p-value was as large as 0.000 (less than 0.05). Green employee behavior is positively and significantly impacted by green organizational culture. The fact that the value of the original sample was 0.425, the value of the t-statistic was 4.114 (higher than 1.96), and the value of the p-value was as large as 0.000 (less than 0.05) establish this.